Maternal and Socio-Demographic Factors Associated with Birth Weight of Newborns Delivered at a Teaching Hospital of Dhaka City - Afrin, Sadia; Rahman, Anisur; Ahammed, Afsar; Afrin, Shaila; Sarker, Md Khalequzzaman; Hossain, Ahmed (Journal of Current and Advance Medical Research, 2019)
Background: Birth weight is the most important predictor of newborn health and survival and is associated with higher risk of infant and childhood mortality. Objective: The objective of this study was to assess the maternal and socio-demographic factors of low birth weight (LBW) newborns of mothers admitted at a teaching medical college hospital in Dhaka city of Bangladesh. Methodology: This was a cross sectional study. Interview was taken by face to face interview and was focused to obtain the information about maternal weight at onset gestation, before delivery, educational, economical status of family, antenatal care visits, maternal exposure to hypertension and anaemia. Data had been collected from interview and medical records. Results: This study revealed from multivariate liner regression analysis. In this model, birth weight had been considered as continuous variable and results had depicted the relationship of different maternal factors with birth weight. This study suggests that there were several factors which lead to LBW babies. The study shows ANC visits (p value 0.05), number of parity (p value .02) and hypertension (p value 0.02) had significant negative effect of on birth weight. Mothers who had taken less ANC visits, more chance of having LBW.Hypertensive mothers were at risk of having low birth weight babies than normotensive mothers. Number of parity was also found as a significant factor. Primi mothers were more prone to LBW. Conclusion: This study suggests that less ANC visits, increase number of parity and hypertension have significant negative effect of on birth weight. Journal of Current and Advance Medical Research 2019;6(1):47-52